The Boundary of Lithium Plating in Graphite Electrode for Safe Lithium‐Ion Batteries. Issue 23 (5th May 2021) - Cai, Wenlong; Yan, Chong; Yao, Yu‐Xing; Xu, Lei; Chen, Xiao‐Ru; Huang, Jia‐Qi; Zhang, Qiang
Abstract: Uncontrolled Li plating in graphite electrodes endangers battery life and safety, driving tremendous efforts aiming to eliminate Li plating. Herein we systematically investigate the boundary of Li plating in graphite electrode for safe lithium‐ion batteries. The cell exhibits superior safety performance than that with Li dendrites by defining the endurable amount of uniform Li plating in graphite anode. The presence of "dead Li" can be eliminated owing to the uniform distribution of Li plating, and the average Coulombic efficiency for deposited Li during reversible plating/stripping process is decoupled as high as about 99.5 %. Attributing to the limited Li plating with superior Coulombic efficiency, the LiNi0.5 Mn0.3 Co0.2 O2 | graphite cell achieves a high capacity retention of 80.2 % over 500 cycles. This work sheds a different light on further improving the fast‐charging capability, low‐temperature performance, and energy density of practical lithium‐ion batteries. Abstract : The boundary of Li plating in a graphite electrode for safe lithium‐ion batteries is defined. The cell with regulated Li plating exhibits highly reversible Li plating/stripping Coulombic efficiency >99.5 % with superior safety performance, offering a strategy to achieve safe high‐energy fast‐charging lithium‐ion batteries.